Who made the paintings: Artists or artificial intelligence? The effects of identity on liking and purchase intention - Gu, Li; Li, Yong (Frontiers in Psychology, 2022)
Investigating how people respond to and view AI-created artworks is becoming increasingly crucial as the technology's current application spreads due to its affordability and accessibility. This study examined how AI art alters people’s evaluation, purchase intention, and collection intention towards Chinese-style and Western-style paintings, and whether the art expertise plays a role. Study 1 recruited participants without professional art experience (non-experts) and found that who made the paintings would not change their liking rating, purchase intention, and collection intention. In addition, they showed ingroup preference, favoring Chinese-style relative to Western-style paintings, in line with previous evidence on cultural preference in empirical aesthetics. Study 2 further investigated the modulation effect of art expertise. Art experts evaluated less favorably (less liking, lower purchase and collection intentions) AI-generated paintings relative to artists-made paintings, while non-experts showed no preference. There was also an interaction effect between the author and the art expertise, and interaction between the painting style and the art expertise. Collectively, the findings in the current study showed that who made the art matters for experts and that the painting style affects aesthetic evaluation and ultimate reception of it. These results would also provide implications for AI-art practitioners.